1995
DOI: 10.1159/000119167
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Case Report: Opiate Antagonist and Event-Related Desynchronization in 2 Autistic Boys

Abstract: Event-related desynchronization and visual orientational behavior were examined in 2 autistic boys to determine if blockade of endogenous opioid activity facilitates cognitive processing at a cortical level. Before naltrexone, the boys showed no selective alpha blocking during exposure to either mother’s pictures or white light. Unlike normals, they exhibited strong alpha band enhancement at temporocentral recording sites. Two hours after administering 0.5 mg/kg naltrexone, mother- as well as light-related alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Properties of N-and C-Terminally Modified Analogues Using a δ 1 Receptor Agonist. Elimination of the carboxylate function of H-Dmt-Tic-OH substantially increased the µ affinity of di-and tripeptide derivatives (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) (Figure 1 and Table 1). The net effect was the loss of δ-opioid selectivity and the appearance of compounds that were either essentially nonselective (6, 9, 10, and 15), weakly µ-selective (8, 11, and 16), or moderately µ-selective (12).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Properties of N-and C-Terminally Modified Analogues Using a δ 1 Receptor Agonist. Elimination of the carboxylate function of H-Dmt-Tic-OH substantially increased the µ affinity of di-and tripeptide derivatives (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) (Figure 1 and Table 1). The net effect was the loss of δ-opioid selectivity and the appearance of compounds that were either essentially nonselective (6, 9, 10, and 15), weakly µ-selective (8, 11, and 16), or moderately µ-selective (12).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the nonalkylated, C-terminally modified dipeptides 11 and 12 lacked δ antagonism; however, 11 surprisingly manifested a weak δ agonism and moderate µ agonism despite its high δ affinity (Table 1) while other analogues (7, 13, 14, and 17) also produced anomalous biological activities on MVD and GPI (Table 2) relative to their receptor binding parameters (Table 1). H-Dmt-Tic-NHMe (7) had extraordinarily weak δ agonism with low µ antagonism, while its Ala-tripeptide derivative (17) gave very weak δ and µ agonism. Despite the high δ receptor affinity of compound 14, the bioactivity data indicated only modest δ antagonism and weak µ antagonism.…”
Section: Receptor Binding Competition Against a Highlymentioning
confidence: 98%
See 1 more Smart Citation
“…Although there is a case study of a paradoxical increase in self-injurious behavior in an autistic adult after administration of an opiate blocker (Benjamin, Seek, Tresise, Price, & Gagnon, 1995), drug trial studies have found that the opiate blockers naltrexone and naloxone reduce self-injurious behaviors and gaze aversion, and inconsistently show beneficial effects on social behavior (Gillberg, 1995). These effects are hypothesized to result from abnormal opioid activity—including both high and low levels—in the brains of some autistic individuals (2 of 2 cases, Akkok, 1995; 41 of 41, Campbell et al, 1993; 13 of 13, Ernst et al, 1993; 2 of 2, Knabe & Bovier, 1992; 8 of 13, Kolmen, Feldman, Handen, & Janosky, 1995; 2 of 2, Lensing et al, 1995; 46 of 55, Sandman, 1991; 7 of 12, Scifo et al, 1991; 2 of 2, Smith, Gupta, & Smith, 1995; 1 of 1, Walters, Barrett, Feinstein, Mercurio, & Hole, 1990).…”
Section: Question 1: Does Neural Evidence Support the Proposed Dysfun...mentioning
confidence: 99%
“…Treatment with naltrexone to block opioid receptors was first carried out by Panksepp et al Results indicated a reversal in autistic behaviors and gaze aversion at doses of 0.5, 1.0, and 2.0 mg/kg. (Lensing et al, 1995 ) There was no consensus regarding the optimal dose. (Campbell et al, 1989 ) The few published reports on naltrexone for autism found benefit for some patients but not for others (Campbell et al, 1993 ).…”
Section: Introductionmentioning
confidence: 99%